2022
DOI: 10.1113/ep090266
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in hypobaric hypoxia increases markers of intestinal injury and symptoms of gastrointestinal distress

Abstract: New Findings What is the central question of this study?What is the effect of hypobaric hypoxia on markers of exercise‐induced intestinal injury and symptoms of gastrointestinal (GI) distress? What is the main finding and its importance?Exercise performed at 4300 m of simulated altitude increased intestinal fatty acid binding protein (I‐FABP), claudin‐3 (CLDN‐3) and lipopolysaccharide binding protein (LBP), which together suggest that exercise‐induced intestinal injury may be aggravated by concurrent hypoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
2
11
5
Order By: Relevance
“…Furthermore, our findings of increased MCP-1, TNF-α, IL-1β, and IL-10 expand upon our previous work and confirm the work of Hill et al (36), who demonstrated that exercise in hypoxia increases the circulation of both proinflammatory and anti-inflammatory cytokines. However, in contrast to our previous study (8), the present findings show that exercise in hypoxia alone (i.e., placebo trial) was not sufficient to increase LBP. This was somewhat surprising given the large effect size ( d = 1.12) that we previously reported, although this discrepancy is likely explained by differences in exercise intensity (8).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, our findings of increased MCP-1, TNF-α, IL-1β, and IL-10 expand upon our previous work and confirm the work of Hill et al (36), who demonstrated that exercise in hypoxia increases the circulation of both proinflammatory and anti-inflammatory cytokines. However, in contrast to our previous study (8), the present findings show that exercise in hypoxia alone (i.e., placebo trial) was not sufficient to increase LBP. This was somewhat surprising given the large effect size ( d = 1.12) that we previously reported, although this discrepancy is likely explained by differences in exercise intensity (8).…”
Section: Discussioncontrasting
confidence: 99%
“…As expected, exercise in hypoxia increased markers of intestinal cell injury, intestinal permeability, microbial translocation, and inflammation, which partly confirm and build upon our previous findings (8). Indeed, here we report that exercise at simulated 4300 m caused intestinal injury, as noted by the preexercise to postexercise increases in I-FABP and I-BABP.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations